Identification of Novel Serine/Threonine Protein Phosphatases in Trypanosoma cruzi: a Potential Role in Control of Cytokinesis and Morphology - Orr, George A. (American Society for Microbiology, 2000)
We cloned two novel Trypanosoma cruzi proteins by using degenerate oligonucleotide primers prepared against conserved domains in mammalian serine/threonine protein phosphatases 1, 2A, and 2B. The isolated genes encoded proteins of 323 and 330 amino acids, respectively, that were more homologous to the catalytic subunit of human protein phosphatase 1 than to those of human protein phosphatase 2A or 2B. The proteins encoded by these genes have been tentatively designated TcPP1α and TcPP1β. Northern blot analysis revealed the presence of a major 2.3-kb mRNA transcript hybridizing to each gene in both the epimastigote and metacyclic trypomastigote developmental stages. Southern blot analysis suggests that each protein phosphatase 1 gene is present as a single copy in the T. cruzi genome. The complete coding region for TcPP1β was expressed in Escherichia coli by using a vector, pTACTAC, with the trp-lac hybrid promoter. The recombinant protein from the TcPP1β construct displayed phosphatase activity toward phosphorylase a, and this activity was preferentially inhibited by calyculin A (50% inhibitory concentration [IC(50)], ∼2 nM) over okadaic acid (IC(50), ∼100 nM). Calyculin A, but not okadaic acid, had profound effects on the in vitro replication and morphology of T. cruzi epimastigotes. Low concentrations of calyculin A (1 to 10 nM) caused growth arrest. Electron microscopic studies of the calyculin A-treated epimastigotes revealed that the organisms underwent duplication of organelles, including the flagellum, kinetoplast, and nucleus, but were incapable of completing cell division. At concentrations higher than 10 nM, or upon prolonged incubation at lower concentrations, the epimastigotes lost their characteristic elongated spindle shape and had a more rounded morphology. Okadaic acid at concentrations up to 1 μM did not result in growth arrest or morphological alterations to T. cruzi epimastigotes. Calyculin A, but not okadaic acid, was also a potent inhibitor of the dephosphorylation of (32)P-labeled phosphorylase a by T. cruzi epimastigotes and metacyclic trypomastigote extracts. These inhibitor studies suggest that in T. cruzi, type 1 protein phosphatases are important for the completion of cell division and for the maintenance of cell shape.